Hubungan Gaya Hidup Dengan Kejadian Hipertensi Pada Lansia di Wilayah Kerja Puskesmas Pasar Ikan Kota Bengkulu Tahun 2025 - Tati Herpianti; Sulastri Sulastri; Meri Epriana (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Hypertension is a non-communicable disease that frequently occurs in the elderly and represents a serious health issue due to its potential for various complications. One of the factors influencing the occurrence of hypertension is lifestyle, including dietary patterns, physical activity, smoking habits, and rest patterns. This study aims to determine the relationship between lifestyle and the incidence of hypertension among the elderly in the working area of the Pasar Ikan Community Health Center, Bengkulu City, in 2025. This research utilized an analytical design with a cross-sectional approach. The sample was selected using an accidental sampling technique, totaling 38 respondents. The instruments used were a lifestyle questionnaire and blood pressure measurements. Data analysis was conducted at univariate and bivariate levels using the Chi-Square test with a significance level of α = 0.05. The results showed that most respondents had an unfavorable lifestyle (20 people, 52.6%), while 18 people (47.4%) had a favorable lifestyle. Bivariate analysis indicated a significant relationship between lifestyle and the incidence of hypertension among the elderly at the Pasar Ikan Community Health Center, Bengkulu City, in 2025 (p-value 0.001 < 0.05). In conclusion, this study can serve as reference material to enhance knowledge regarding healthy lifestyles in the elderly. Therefore, the health center is expected to increase promotive and preventive efforts through health education on healthy lifestyle implementation—such as regular physical activity, a balanced diet, adequate rest, and avoiding smoking—to prevent and control hypertension in the elderly.